2014
DOI: 10.1146/annurev-publhealth-032013-182510
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss in an Aging American Population: Extent, Impact, and Management

Abstract: Despite contributing substantially to disability in the United States, agerelated hearing loss is an underappreciated public health concern. Loss of hearing sensitivity has been documented in two-thirds of adults aged 70 years and older and has been associated with communication difficulties, lower health-related quality of life, and decreased physical and cognitive function. Management strategies for age-related hearing loss are costly, yet the indirect costs due to lost productivity among people with communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
134
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(147 citation statements)
references
References 62 publications
6
134
0
7
Order By: Relevance
“…Banh, Singh, and Pichora-Fuller (2012) also found that older adults with normal hearing thresholds through 4.0 kHz had significantly lower scores on the SSQ (i.e., less perceived difficulty) as compared with those of younger adults with normal hearing (Banh et al, 2012), supporting the idea that at least some older adults may underestimate hearing problems. Moreover, Bainbridge and Wallhagen's (2014) finding that a proportion of middle-aged individuals who have minimal hearing loss (in terms of puretone thresholds) feels that they experience hearing problems is consistent with the results of Glyde et al (2013), which demonstrated that performance can decline on complex listening tasks even when thresholds are within normal limits.In summary, research on age-related changes in speech perception confirms the problems that audiologists hear from their clients: Speech understanding in complex listening situations is effortful and challenging for many middle-aged and older adults. In the sections below, we summarize results from several studies conducted in our lab that were designed to identify the types of listening situations that are particularly difficult as people age and how degree of hearing loss and selected cognitive abilities help explain individual variability in these situations.…”
supporting
confidence: 82%
“…Banh, Singh, and Pichora-Fuller (2012) also found that older adults with normal hearing thresholds through 4.0 kHz had significantly lower scores on the SSQ (i.e., less perceived difficulty) as compared with those of younger adults with normal hearing (Banh et al, 2012), supporting the idea that at least some older adults may underestimate hearing problems. Moreover, Bainbridge and Wallhagen's (2014) finding that a proportion of middle-aged individuals who have minimal hearing loss (in terms of puretone thresholds) feels that they experience hearing problems is consistent with the results of Glyde et al (2013), which demonstrated that performance can decline on complex listening tasks even when thresholds are within normal limits.In summary, research on age-related changes in speech perception confirms the problems that audiologists hear from their clients: Speech understanding in complex listening situations is effortful and challenging for many middle-aged and older adults. In the sections below, we summarize results from several studies conducted in our lab that were designed to identify the types of listening situations that are particularly difficult as people age and how degree of hearing loss and selected cognitive abilities help explain individual variability in these situations.…”
supporting
confidence: 82%
“…Diese Hörhilfen können zwar das Sprachverständnis in verschiedensten Hörsituation erheblich verbessern. Allerdings kann die gewohnte normale Hörfähigkeit nicht mehr wiederherstellt werden [15].…”
Section: Hintergrundunclassified
“…Nach epidemiologischen Studien liegt die Prävalenz von erworbener Schwerhörigkeit in den Vereinigten Staaten bei 45,1 % bei Menschen im Alter von 45-74 Jahren [17], bei 63,1 % im Alter von70Jahrenoderälter [18] und steigt im Alter deutlich an [15,19]. Altersschwerhörigkeit tritt häufiger bei Männern als bei Frauen auf [17,20].…”
Section: Hintergrundunclassified
See 1 more Smart Citation
“…DM has recently been of considerable concern for public health since its complications increase morbidity and mortality in patients; even studies have also found that patients with DM may suffer from hearing impairment (Powers, 2015a). Hearing loss is a more common issue in public health nowadays and it is prevalent in approximately two-thirds of the geriatric population (>70 years) (Bainbridge and Wallhagen, 2014). The effect of hearing loss may impair the quality of life of patients which affects functional, social, as well as psychological aspects (Ciorba et al, 2012).…”
Section: Introductionmentioning
confidence: 99%